2000
DOI: 10.1364/josaa.17.001505
|View full text |Cite
|
Sign up to set email alerts
|

Motion perception at scotopic light levels

Abstract: Although the spatial and temporal properties of rod-mediated vision have been extensively characterized, little is known about scotopic motion perception. To provide such information, we determined thresholds for the detection and identification of the direction of motion of sinusoidal grating patches moving at speeds from 1 to 32 deg/s, under scotopic light levels, in four different types of observers: three normals, a rod monochromat (who lacks all cone vision), an S-cone monochromat (who lacks M-and L-cone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 85 publications
(112 reference statements)
1
28
0
Order By: Relevance
“…Gegenfurtner, Mayser, and Sharpe (2000) revealed that the motion detection threshold did not change between photopic and scotopic vision, whereas the perceptual speed of the moving stimulus decreased approximately 20% with scotopic vision, as compared with photopic vision, if the temporal frequency of the stimulus was below 4 Hz.…”
Section: Vection Is Weakened By Red Visual Stimulimentioning
confidence: 90%
See 1 more Smart Citation
“…Gegenfurtner, Mayser, and Sharpe (2000) revealed that the motion detection threshold did not change between photopic and scotopic vision, whereas the perceptual speed of the moving stimulus decreased approximately 20% with scotopic vision, as compared with photopic vision, if the temporal frequency of the stimulus was below 4 Hz.…”
Section: Vection Is Weakened By Red Visual Stimulimentioning
confidence: 90%
“…The results of Experiment 7 were also contrary to the expectation; that is, vection yielded by the moving red grating was weaker than that yielded by the green grating. Moreover, we used 5.8-Hz motion stimuli in Experiment 7, which is sufficiently faster than 4 Hz (Gegenfurtner et al, 2000). In addition, Grossman and Blake (1999) revealed that there was no difference in the coherent motion threshold between photopic and scotopic vision.…”
Section: Vection Is Weakened By Red Visual Stimulimentioning
confidence: 99%
“…Human motion perception indeed changes as light intensity decreases. Velocity perception (Gegenfurtner, Mayser, & Sharpe, 2000;Hammett, Champion, Thompson, & Morland, 2007;Pritchard & Hammett, 2012;Vaziri-Pashkam & Cavanagh, 2008), velocity discrimination thresholds (Takeuchi & De Valois, 2000), short-range motion perception (Dawson & Di Lollo, 1990), complex-motion perception (Billino, Bremmer, & Gegenfurtner, 2008), biological-motion perception (Billino et al, 2008;Grossman & Blake, 1999), perception of static-motion illusions (Hisakata & Murakami, 2008), perception of interstimulus interval (ISI) reversal (Sheliga, Chen, FitzGibbon, & Miles, 2006;Takeuchi & De Valois, 1997Takeuchi, De Valois, & Motoyoshi, 2001), perception of two-stroke motion (Challinor & Mather, 2010;Mather & Challinor, 2009), the coherent-motion threshold (Billino et al, 2008;Lankheet, van Doorn, & van de Grind, 2002;van de Grind, Koenderink, & van Doorn, 2000), moving texture segregation (Takeuchi, Yokosawa, & De Valois, 2004), and visual motion priming (Takeuchi, Tuladhar, & Yoshimoto, 2011;Yoshimoto & Takeuchi, 2013) have all been shown to vary with the light level.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of this dramatic luminance change on speed perception has not yet received much attention. Gegenfurtner, Mayser, and Sharpe (2000) showed that under scotopic light levels there is a decrease in the perceived speed of motion with decreasing luminance at rates below 4 Hz. In their study, deuteranopic subjects were tested and the procedure was set so that the stimuli solely affected the rod cells in the retina and thus the speed underestimation perceived there was due to the isolated stimulation of the rods.…”
Section: Introductionmentioning
confidence: 99%